Cuartetero and Cordoban, or Cordoban and cuartetero? Variations in the musical identity discourses of the Cordoban quartet in the nineties. (Revista Argentina de Musicología, 2024)
In this work we start from the idea that the meaning, specifically of popular music, cannot be considered fixed or immanent. In the same way, we understand that music can produce different effects, but not just any, and some interpretations, taking into account the interpretative rules of a society at a given time, are presented as preferable, so that they condition the interaction of users with them. This conditioning is what makes certain music better serve the identity constructions of certain users at a particular historical moment.Taking this approach into account, we address the construction of two identity discourses in the Córdoba quartet, a popular music from the Argentine interior, during the 1990s: on the one hand, a quartet identity in the proposal of Carlos “La Mona” Jiménez and, on the other, a Cordoba identity, in Rodrigo's proposal. The illustration of our conclusions focuses on the analysis of lyrics and music of two songs released between the mid and late 1990s: “Cuarte Conga” and “Soy Cordobés”.
Keywords: Identity discourse; Cordoban Quartet; La Mona Jiménez; Rodrigo